2016
DOI: 10.1002/cbdv.201600048
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antioxidant Activity of Essential Oils and Methanol Extracts of Different Parts from Juniperus rigida Siebold & Zucc.

Abstract: The chemical composition and antioxidant activity of essential oils and MeOH extracts of stems, needles, and berries from Juniperus rigida were studied. The results indicated that the yield of essential oil from stems (2.5%) was higher than from needles (0.8%) and berries (1.0%). The gas chromatography/mass spectrometer (GC/MS) analysis indicated that 21, 17, and 14 compounds were identified from stems, needles, and berries essential oils, respectively. Caryophyllene, α-caryophyllene, and caryophyllene oxide w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 37 publications
(31 reference statements)
1
13
0
Order By: Relevance
“…Despite the widespread application and commercial importance of Juniperus -derived products, evaluation of J. rigida has traditionally been based on morphological characteristics resulting from natural genetic development (e.g., mutation, recombination) of individual species with little consideration of phytochemical components and bioactivities (Li et al, 2014; Liu Q. X. et al, 2016; Sobierajska et al, 2016). These shortcomings have limited the utilization of J. rigida , highlighting the urgent necessity for a simple and flexible approach for quality evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the widespread application and commercial importance of Juniperus -derived products, evaluation of J. rigida has traditionally been based on morphological characteristics resulting from natural genetic development (e.g., mutation, recombination) of individual species with little consideration of phytochemical components and bioactivities (Li et al, 2014; Liu Q. X. et al, 2016; Sobierajska et al, 2016). These shortcomings have limited the utilization of J. rigida , highlighting the urgent necessity for a simple and flexible approach for quality evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…These results were in keeping with the total chemical composition contents of seed oil, meaning that antimicrobial activity is closely relative to the FAs and other phytochemicals contained in seed oils. Meng et al [24] and Liu et al [25] also proved the similar results on seed oils from Juniperus rigida. Moreover, the results has been previously confirmed and showed that natural seed oil from plants had prevention and treatment effects based on the biological activities, such as anti-inflammatory, anticancer, and antiviral properties, antimicrobial activity may be considered as an important application feature or parameter in quality evaluation of tree peony seed oils.…”
Section: Antimicrobial Activity Of Different Tree Peony Cultivarsmentioning
confidence: 56%
“…These results were consistent with the change profile of oil yields and FAs contents of ten tree peony varieties, supporting the fact that FA compositions, such as, palmitic acid, stearic acid, oleic acid, linoleic acid, and α-linolenic acid, play important roles in the antioxidant activity of seed oil in tree peony [15] and other oleaginous plants. [24,25] The strong antioxidant activities found in samples FD, ZB and YPTJ may attribute to the high amounts of UFAs (oleic acid, linoleic acid, α-linolenic acid). Similar results were also be confirmed in previous reports described by Zhang et al, [15] involved in wild tree peony species and its cultivars.…”
Section: Bioactivity Of Different Tree Peony Cultivarsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chlorogenic acid and podophyllotoxin were the most abundant phenolic compounds in LE. There were lower contents of each phenolic compound in J. rigida litter aqueous extract than in needle, berry and stem samples of J. rigida . This phenomenon may be due to phenolic compounds directly or indirectly releasing into soil, plant roots or the environment through leaching, volatilization and residual decomposition…”
Section: Resultsmentioning
confidence: 90%